DEWAN PENDIDIKAN DI TENGAH PUSARAN COVID-19 - kholilur Rahman (Universitas Yudharta Pasuruan, 2019)
It is probably almost a consensus of experts that the Covid-19 pandemic is an undiscovered virus, and its negative impact touches almost the entire joints of human life; Social, economic, banking, tourism, and education. The impact of the life joints mentioned at the beginning may be overcome by certain stimuli and within a certain period of time can be recovered. But the impact that touches the joints of the last Life (education), especially related to the quality of education, the Resolution requires